Automatic genetic planning for volumetric modulated arc therapy: A large multi-centre validation for prostate cancer. (July 2020) - Fiandra, Christian; Rossi, Linda; Alparone, Alessandro; Zara, Stefania; Vecchi, Claudio; Sardo, Anna; Bartoncini, Sara; Loi, Gianfranco; Pisani, Carla; Gino, Eva; Ruo Redda, Maria Grazia; Marco Deotto, Gian; et al.
Highlights: Creation of manual plans is labor intensive with quality depending on planner. A novel genetic optimization (GPS) for VMAT auto-planning is presented. GPS was tested without centre-specific configuration. Validation with ten centres, including in total 100 patients is presented. Abstract: Purpose: The first clinical genetic autoplanning algorithm (Genetic Planning Solution, GPS) was validated in ten radiotherapy centres for prostate cancer VMAT by comparison with manual planning (Manual). Methods: Although there were large differences among centres in planning protocol, GPS was tuned with the data of a single centre and then applied everywhere without any centre-specific fine-tuning. For each centre, ten Manual plans were compared with autoGPS plans, considering dosimetric plan parameters and the Clinical Blind Score (CBS) resulting from blind clinician plan comparisons. AutoGPS plans were used as is, i.e. there was no patient-specific fine-tuning. Results: For nine centres, all ten plans were clinically acceptable. In the remaining centre, only one plan was acceptable. For the 91% acceptable plans, differences between Manual and AutoGPS in target coverage were negligible. OAR doses were significantly lower in AutoGPS plans ( p  < 0.05); rectum D15% and Dmean were reduced by 8.1% and 17.9%, bladder D25% and Dmean by 5.9% and 10.3%. According to clinicians, 69% of the acceptable AutoGPS plans were superior to the corresponding Manual plan. In case of preferred Manual plans (31%), perceived advantages compared to autoGPS were minor. QA measurements demonstrated that autoGPS plans were deliverable. A quick configuration adjustment in the centre with unacceptable plans rendered 100% of plans acceptable. Conclusion: A novel, clinically applied genetic autoplanning algorithm was validated in 10 centres for in total 100 prostate cancer patients. High quality plans could be generated at different centres without centre-specific algorithm tuning.